Effect of different fertigation levels and drip layouts on the performance of okra under plastic mulching - ASWATHY K; Preeti Kumari; Er. Anu Varughese (Guide) (Tavanur 2012 Department of Irrigation And Drainage Engineering)
Effect of different fertigation levels and drip layouts on the performance of okra under plastic mulching
Effect of different fertigation levels and drip layouts on the performance of okra under plastic mulching